Effect of nap opportunity on physiological responses and specific abilities in elite basketball players - Souabni, M.; Hammouda, O.; Souabni, M. J.; Romdhani, M.; Driss, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Sleep disturbances are common among elite athletes on training days, night(s) before and following competitions in elite athletes. It was showed that sleep deprivation deteriorates athletes` physical and cognitive performance, increases muscle damage, impairs the recovery from high-intensity exercise, and is associated with higher injury risk. According Souabni et al. [1], napping is a safe and non-invasive intervention in athletes` schedules. However, studies investigating the effect of napping on physical performance showed inconclusive and contradictory results. This study investigates the effect of 40-min nap opportunity on physiological responses and specific abilities in elite basketball players